Laparoendoscopic Single-site Adrenalectomy versus Conventional Laparoscopic Adrenalectomy: An Updated Meta Analysis - Wu, Shike; Lai, Hao; Zhao, Jiangyang; Chen, Jiansi; Mo, Xianwei; Zuo, Hongqun; Lin, Yuan (Urology Journal, 2016)
Purpose: Previous meta-analyses that compared the outcome of laparoendoscopic single-site adrenalectomy (LESSA) and conventional laparoscopic adrenalectomy (CLA) have not shown consistent results. The aim of this meta-analysis was to reassess current evidence regarding the efficacy and safety of LESSA versus CLA. Materials and Methods: A literature search of PubMed, Embase, Medline, and the Cochrane Library was performed to identify eligible articles up until September 2015. Quantitative variables were calculated using the weighted mean differences (WMDs), and qualitative variables were pooled using odds ratios (ORs). Results: Ten retrospective studies, including a total of 704 cases, were identified. Patients in the LESSA group benefitted from shorter length of hospital stay (95% confidence interval [CI]: -1.27 to -0.36, WMD: -0.81, P < .001) and better postoperative pain scores (95% CI: -1.51 to -0.99, WMD: 1.25, P < .001). There was no significant difference between the two techniques in operative time, estimated blood loss, resumption of oral intake, dose of analgesic required, perioperative complications, conversion, transfusion, or pain medications required. Conclusions: Based on current evidence, LESSA appear to be a safe and feasible alternative to CLA with a shorter length of hospital stay and lower postoperative pain scores in certain patients. We await high-quality, double-blind randomized clinical trials with long-term follow-up to confirm and update the findings of this analysis; future studies should focus on failure of technique, cosmesis, and cost.